QUALITY OF LIFE DITINJAU DARI SPIRITUAL WELL-BEING PADA MAHASISWA KEPENDETAAN DI SEKOLAH TINGGI THEOLOGIA INJILI INDONESIA MEDAN-SUMATERA UTARA - Delviana Buulolo (Universitas HKBP Nommensen, 2019)
This study aims to find out relationship between quality of life and spiritual well-being. The hypothesis proposed in this study states that there is a positive relationship between quality of life and spiritual well-being, assuming that the higher is spiritual well-being, the higher quality of life will be and conversely the lower is the spiritual well-being, the lower will the quality of life be. The subjects of this study were 80 student on on the evangelical theological seminary of Indonesia Medan. Data were obtained from a scale to measure quality of life and spiritual well-being. The calculation was performed by testing requirements analysis (assumption test), which consisting of normality test and linearity test. Data analysis was performed by using Product Moment Correlation Analysis through SPSS 18 for Windows. The results of data analysis showed that r = 0.405 and p = 0.000 (p < 0.05), which indicates that there is a positive relationship between quality of life and spiritual well-being. The results indicate that the contribution of the given variable, quality of life and spiritual well-being is 16.4 percent, while the remaining 83.6 percent is influenced by other factors not examined in this study. From these results, it is concluded that the hypothesis stating that there is a positive relationship between quality of life and spiritual well-being.